Russian UN-delegate Gromyko (left) meets former vice-president Wallace at Lake Success, New York. Text on the back - Broderick, Hugh,
Russian UN-delegate Gromyko (left) meets former vice-president Wallace at Lake Success, New York. Text on the back.